Taxonomic certification versus the scientific method - Rogers, D. Christopher (Zootaxa, 2012)
Over the last 30 years or so there has been an increasing need for organism identification services. This has been the positive result of increased habitat monitoring, particularly as regards water quality. Organism diversity and community structure are used as an overall meter stick of habitat health and functionality, in a method referred to as biomonitoring. To meet the organism identification need, private and government laboratories specializing in identification work have been developed, particularly in North America, Europe and Australia. I myself have worked in this industry and was employed in either government or private laboratories over the last 18 years. These laboratories primarily identify benthic aquatic invertebrates, periphyton, phytoplankton, zooplankton and fish (both freshwater and marine).